Incidence of Einstellung Effect among Programming Students and its Relationship with Achievement - Obispo, Jun Rangie C (Archīum Ateneo, 2018)
The Einstellung effect (EE) refers to an individual’s bias towards a familiar, working solution when solving problems even though more appropriate solutions are available. Prior studies have shown that this fixation may pose some problems when the known solution can no longer be used because this prevents one from being able to generate other solutions. In this paper, we investigate EE in the context of programming and how this phenomenon affects the performance of student programmers in a single laboratory experiment. We observed that about 33% of the students exhibited a full incidence of EE where solutions to three problems used the same category of approaches. Twenty-four percent of students exhibited partial EE, where two of three problems had similar approaches. Forty-two percent of students did not exhibit EE at all. We also observed that students with higher pre-test scores exhibited more incidences of EE. Those who exhibited more EE also performed better in solving the programming problems in terms of the number of correctly implemented plans. This study shows that EE has a positive effect on the performance of student programmers, at least in a single programming activity. This opens opportunities to further explore the effect of EE on the overall performance of students in programming.